AN ENHANCED CROSS LAYER SCHEME FOR BACK OFF ATTACK AND NETWORK LAYER MISBEHAVIOR DETECTION IN MANET . - R. Kumaran & K P K Devan2 (International Journal of Research Science and Management, 2017)
Mobile Ad-Hoc Networks (MANETs) consist of collection of mobile devices with wireless interface. In MANET, each mobile device acts as both router and host. Nodes agree to forward packets, but fail to do because they want to save their resources. They just keep receiving the data destined to them, and drop the data of other nodes without forwarding or routing them, which reduces the throughput of the network. These nodes are called as misbehaving nodes. Misbehaving nodes deviating from the standard MAC (Medium Access Control) protocol can significantly degrade normal nodes performance and are usually difficult to detect. There are very few techniques to detect and isolate the misbehaving nodes using cross-layer detection schemes. In this work, the main aim is to investigate the cross-layer based schemes to reduce the number of false positive rates and to solve the back off misbehavior in MAC layer. This work also aims to propose an optimized cross-layer based detection scheme.